The responsiveness of local government in the Greater Tzaneen Local Municipality - Baloyi, Vonani Ashed Bianca (University of the Free State, 2023)
Despite several reforms over twenty-nine years, such as fostering citizen participation in local government affairs, the responsiveness of local government remains a continued problem in the South African landscape. The ability of governments globally, specifically local governments, to stay responsive to the service delivery needs of their citizenry has become fundamental to addressing increasing demands from citizens, societal challenges and institutional ills (including maladministration, corruption, lack of capacity and incompetence). Responsiveness, which is considered the ability to satisfy an expressed need, preference or value of citizens, is considered fundamental to effective and accountable governance. Thus, this situation warrants an investigation of local government responsiveness in South Africa. The primary focus of this study is the Greater Tzaneen Local Municipality. Through a qualitative research design, this study investigates the responsiveness of the Greater Tzaneen Local Municipality to citizens’ service delivery needs. The findings show that successful government responsiveness during service delivery depends on the local government exercising its leadership, facilitating citizen participation, being transparent to all stakeholders concerned with service delivery, and having the citizens and stakeholders hold its officials accountable. Significantly, this study found that South Africa does indeed have sufficient legislative frameworks to guide local government officials and other interrelated government spheres in addressing service delivery challenges. The study thus, proposes a conceptual framework for enhancing local government responsiveness to citizens’ service delivery needs. Through this framework, the existing legislative frameworks and the integration of citizens in local government decision-making processes can be combined. Furthermore, the findings shed light on the practical implications for local government officials and administrators, as well as citizens of collaborations with cross-sector stakeholders aimed at achieving enhanced local government responsiveness during service delivery.
Dissertation(M.P.A. (Administration))--University of the Free State, 2023
Keywords: Local government responsiveness; Organizational factors; Citizen participation; Transparency; Accountability; Service delivery